Microbial profile of some ready-to-cook frozen food items sold in Dhaka city, Bangladesh - Md. Shamimuzzaman; Rajib Kanti Roy; Toma Rani Majumder; Nirmal Chandra Barman; Nazia Nawshad Lina; Md. Tarek Hasan; Biplab Kumar Dash (Food Science and Human Wellness, 2022)
This study aimed to assess the microbiological quality of 159 animal- and plant-based ready-to-cook (RTC) frozen food items currently popular in Dhaka. Microbiological analyses were carried out to enumerate total aerobic counts of mesophilic bacteria, yeast and mold and to detect some common foodborne pathogens according to standard microbiological criteria. Higher microbial loads in all animal-based food types, other than chicken strips were found. In contrast, plant-based items were relatively safe except paratha, dal-puri, rooti chapati, and aloo-puri. Several common pathogenic bacterial species were screened by analyzing their morphological, cultural, and biochemical characteristics. Escherichia coli was prevalent in most samples, while Salmonella species were least reported. A considerable number of samples exhibited enough microbial loads at infection or intoxication levels.